Bicycle Injuries in Children. Issue 5885 (20th October 1973) - Craft, A. W.; Shaw, D. A.; Cartlidge, N. E. F.
Abstract : An analysis of 405 bicycle accidents in children under 15 years of age resulting in their attendance at hospital has shown that those having accidents while riding modern "high-rise" bicycles suffered head injury and bone fracture and required hospital admission more frequently than did those riding conventional models. "High-rise" accidents tended to occur on newly acquired and borrowed machines, suggesting that lack of experience of the handling properties of these bicycles may be a factor in the causation of accidents.